Examination of the physical and motoric characteristics of elite soccer players according to their positions - Aksoy, D.; Baydemir, B. (Journal of Education and Learning, 2019)
The purpose of the present study was to examine the physical and motoric characteristics of elite soccer players playing at different positions in U21 team. A total of 64 male soccer players participated in the present study (4 goalkeepers, 16 defense players, 21 midfield players, and 23 strikers). The Body Mass Indices of the players were computed by measuring their height and weights. The Yo-Yo Intermittent Recovery 2 Test and the t-test were applied to the players. The VO2max values of the players were computed according to the formula that was developed by Bangsbo et al. The statistical package programs were employed for data analyses. The "Independent Sampling One-Way Variance Analysis" was applied to compare the physical and motoric characteristics of elite soccer players according to their positions. When differences were detected between the measurements, the "Tukey Analysis" was carried out to determine the direction of these differences. The results were evaluated according to (p<0.05) significance level. It was determined that there was a statistically significant difference between the BMI values of elite soccer players according to their positions (p<0.05). It was also determined that the motoric characteristics of the players did not have any significant differences according to their positions (p>0.05). The lowest values were determined in goalkeepers, strikers, midfield players and defense players according to the BMI values of the elite soccer players. This situation might be associated with the fact that in today`s soccer, players show performance in different areas of the field for attack and defense without considering their positions. According to the BMI values of the elite soccer players, the lowest values ??were determined in goalkeepers, strikers, midfield players and defense players; and no differences were detected in terms of motoric characteristics.